2022
DOI: 10.1029/2022jd036493
|View full text |Cite
|
Sign up to set email alerts
|

The “Polar Vortex” Winter of 2013/2014

Abstract: There have been a surprising number of cold winters across North America compared to model projections over the past 20 years resulting in a winter cooling trend in central North America since 2009 (Cohen et al., 2020).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 69 publications
(163 reference statements)
0
3
0
Order By: Relevance
“…The westward tilt of the eddy geopotential heights with altitude is characteristic of a baroclinic structure of the atmospheric column and is strongest in the lower levels of the troposphere. This westward tilt in the eddy geopotential height field supports the upward propagation of Rossby waves 48 , 49 that then converge over Greenland, thereby enforcing the anomalous ridge. In the section “The snow-hydrological effect as a bridge between spring snow cover variability and summer atmospheric response”, we consider the snow-hydrological effect as an explanatory mechanism behind this delayed baroclinic response.…”
Section: Resultsmentioning
confidence: 61%
“…The westward tilt of the eddy geopotential heights with altitude is characteristic of a baroclinic structure of the atmospheric column and is strongest in the lower levels of the troposphere. This westward tilt in the eddy geopotential height field supports the upward propagation of Rossby waves 48 , 49 that then converge over Greenland, thereby enforcing the anomalous ridge. In the section “The snow-hydrological effect as a bridge between spring snow cover variability and summer atmospheric response”, we consider the snow-hydrological effect as an explanatory mechanism behind this delayed baroclinic response.…”
Section: Resultsmentioning
confidence: 61%
“…Recently, several studies used the cluster analysis and the empirical orthogonal function method to identify the SPV stretching events (Cohen et al., 2021, 2022; Ding et al., 2022, 2023; Kretschmer, Cohen, et al., 2018; Kretschmer, Coumou, et al., 2018, Liang Z et al., 2023) and found that their reflective mechanism and tropospheric response closely resemble those of reflecting SSWs (Matthias & Kretschmer, 2020; Messori et al., 2022; Shen et al., 2023; Zou et al., 2024). Further efforts have been made to unveil possible causes and impacts of the SPV stretching events.…”
Section: Introductionmentioning
confidence: 99%
“…The tropospheric vortex exists all year round and extends its edge to midlatitudes, while the stratospheric vortex mainly appears from late fall to early spring at 10 ~ 50 hPa over the Antarctica. The edge of the stratospheric vortex is traditionally identi ed as the peak of potential vorticity gradients along with the great temperature gradients (Cohen et al 2022; Manney et al 2022). Considering the sea-land topographic differences between the Arctic and the Antarctic, planetary waves are less active in the Antarctic, and thus the Antarctic stratospheric vortex is stronger, less distorted, and has a longer lifespan than its northern counterpart (Waugh and Polvani 2010; Rao et al 2020b; Rao and Ren 2020).…”
Section: Introductionmentioning
confidence: 99%